Differences in electric activity of women brain upon testing of simple sensomotor reactions during ovulation and lutein phases - T. Honcharova; N. Filimonova (Vìsnik: Kiïvsʹkij Nacìonalʹnij Unìversitet Imenì Tarasa Ševčenka. Bìologìâ, 2016)
As a result of researches of 10 women 20±2 years in 2 phases of a menstrual cycle it was revealed, that in functional trial "Simple sensomotor reaction" in comparison with functional trial "The open eyes" during the ovulation phase took place the activation of the fronto – parietal systems and the formation of the system top – down control over influence of the increased level of testosterone. While in the lutein phase under the influence of the increased level of a cortisol the formation of the right – hemisphere neural network with attraction of the associative cortex in the context of which the simple sensomotor reaction was realized was observed.